APPLICATION OF MODERN SOFTWARE DIGITALS FOR CREATION OF TOPOGRAPHIC PLANS M 1: 2000 - Шаргар, Елена; Лихва, Антон; Шишкалова, Наталия; Колыханин, Сергей; Стадникова, Наталия (SWorldJournal, 2021)
a theoretical and methodological basis for the use of modern software Digitals to create a cartographic basis of settlements. The possibilities of using the software are analyzed, the theoretical and methodological bases of using the modern Digitals softw